A Snapshot of Gender in Brazil Today : Institutions, Outcomes, and a Closer Look at Racial and Geographic Differences - Gukovas, Renata (World Bank, Washington, DC, 2017)
The Gender Diagnostic: ‘A Snapshot of Gender in Brazil Today: Institutions, Outcomes, and a Closer Look at Racial and Geographic Differences Gender issues in Brazil’ highlights progress on gender equality in the country and lays out the main areas of persisting challenges. It details gender outcomes beyond the national aggregate and emphasizes that gender inequality in Brazil has to be understood at the intersection of gender/location of residence and gender/race.